Development of the Borobudur Conservation Archives services with ICA-AtoM - Asfian, Yannief; Bramantya, Arif Rahman (Universitas Padjadjaran, 2023)
The Borobudur Conservation Office as a memory institution manages its archives and disseminates information about preserving the Borobudur Temple. The Borobudur Conservation Archives have also recognized as a Memory of the World by UNESCO in 2017. Therefore, developing a website using the ICA Atom platform based on open source is important for accessibility of the Borobudur Conservation Archives at the Borobudur Conservation Office. The purpose this study is explain how development of the Borobudur Conservation Archives accessed services through the ICA-AtoM platform with analysis the process of integrating digitized data and the development of the Borobudur Conservation Archives. This study used a qualitative approach with data collection methods: literature study, participatory observation, and interviews. A literature study used library sources related to the research topic. The participatory observation was conducted through fieldwork practices for two months, from 21 December 2020 to 26 February 2021, at the Borobudur Conservation Office. This study used structured and unstructured interviews. The study result was that the development of the ICA-AtoM design had been adapted to the needs of the Borobudur Conservation Office. From the aspect of usage, the developed website https://arsip.borobudurpedia.id has met user needs with standards issued by the International Council on Archives (ICA) and metadata standards. In conclusion, the development of the ICA AtoM platform version 2.5 and the creation of archival information contextualized as shared content for users with evidentiary value, informational value, and intrinsic value are uploaded to the website, including archival descriptions, authority records, and archival institutions.